1996
DOI: 10.1111/j.1399-0039.1996.tb02684.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional significance of polymorphism among MHC class II gene promoters

Abstract: The functional significance of polymorphism among MHC class II promoters in man and mouse is here reviewed, mainly in terms of the hypothesis of differential expression. The hypothesis proposes that differences between antigen-presenting cells in MHC class II expression exert a co-dominant effect on the Th1-Th2 cytokine balance, such that class II molecules of one type come to control to a greater extent the production of one group of cytokines, and those of another type the production of the alternative group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 103 publications
1
21
0
Order By: Relevance
“…It suggests that differential expression may play a role in the control of disease susceptibility by MHC class II genes. Differential expression is also in line with the distribution of polymorphism across MHC class II genes, which is high not only in the peptide-binding domains but also in the promoter region (promoter polymorphism is less evident in MHC class I genes) (2,29). Significantly, this polymorphism in the mouse is highest in the region of the X and Y boxes, where transcription factors bind; it has been suggested that heterozygosity in this region may confer increased fitness through immunological flexibility (29).…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…It suggests that differential expression may play a role in the control of disease susceptibility by MHC class II genes. Differential expression is also in line with the distribution of polymorphism across MHC class II genes, which is high not only in the peptide-binding domains but also in the promoter region (promoter polymorphism is less evident in MHC class I genes) (2,29). Significantly, this polymorphism in the mouse is highest in the region of the X and Y boxes, where transcription factors bind; it has been suggested that heterozygosity in this region may confer increased fitness through immunological flexibility (29).…”
Section: Resultsmentioning
confidence: 54%
“…Differential expression of protective MHC class II molecules in the various antigen-presenting cells (APCs) is one hypothesis that has been proposed to explain the protective effect (2,5,10,11), although other possibilities remain open (3,12). The findings leading to the present study are as follows.…”
mentioning
confidence: 82%
“…Of these, overdominant selection for multiple expression phenotypes has been a primary hypothesis for the maintenance of MHC class II promoter region diversity (22,61). This is based on the idea that functional cis-regulatory diversity within an individual confers additional range and f lexibility in important parameters of transcriptional output (e.g., site, timing, and responsiveness to cytokines), which facilitates a more precise, context-specific immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The overall importance of proper immune regulation, the observed population genetic diversity of the DQA1 promoter in humans (19)(20)(21), and the demonstrated functional significance of this diversity make the proximal promoter region of DQA1 a likely target of natural selection (22). To explore this possibility, we investigated the evolutionary history of the DQA1 proximal promoter region in primates and characterized cis-regulatory variation at both the nucleotide and functional levels.…”
mentioning
confidence: 99%
“…Some MHC class II promoters are highly polymorphic, to an extent that indicates that they must be under selective pressure (Guardiola et al 1996). In contrast, MHC class I promoters are relatively constant (Cereb & Yang 1994;Yao et al 1995).…”
mentioning
confidence: 99%